Sustainability certifications, approaches, and tools for oil palm in Indonesia and Malaysia - Peteru, S.; Komarudin, H.; Brady, M.A. (European Forest Institute, 2022)
Various approaches and tools have been developed to promote sustainable production of palm oil, including sustainability standards and certification systems (both voluntary and mandatory), jurisdictional approaches as a pathway for sustainable sourcing of commodities within political boundaries, and tools assessing sustainability performance. This study (part of the broader EU-funded KAMI – Sustainability of Indonesian and Malaysian Palm Oil - project) compares existing sustainability certifications, approaches, and tools addressing the oil palm sector in Malaysia and Indonesia, especially in regard to environmental thresholds, inclusion of smallholders, social protections including for indigenous peoples, and operational modalities.